Concomitant cisplatin and extended field radiation therapy in patients with cervical and endometrial cancer. Issue 5 (1st August 2002) - Sood, B. M.; Timmins, P. F.; Gorla, G. R.; Garg, M.; Anderson, P. S.; Vikram, B.; Goldberg, G. L.
Abstract : The purpose of this study is to evaluate the toxicity and safety of concomitant cisplatin (CDDP) and extended field radiation therapy (EFRT) in patients with cervical cancer (CxCA) and endometrial cancer (EnCA). Twenty-five patients were analyzed retrospectively for treatment-related morbidity from 1989 to 1998. Fourteen patients had CxCA and 11 patients had EnCA. Eighteen patients (72%) had surgery prior to radiotherapy and chemotherapy. EFRT was delivered by a four-field technique to the pelvis and para-aortic regions. CDDP at 100 mg/m 2 was given over 5 days during 1st and 4th week of EFRT. EFRT dose for EnCA and CxCA was 45 Gy. Toxicity was analyzed using the RTOG toxicity criteria. Twenty-four (96%) of the 25 patients completed the prescribed therapy. Of the 14 patients with CxCA, three (21%) had no toxicity, three (21%) had grade 1–2, and eight (58%) had grade 3–4 hematologic toxicities. Overall six (24%) had grade 3–4 acute gastrointestinal toxicities, three (21%) of these patients were treated for cervix cancer and three (27%) patients were treated for endometrial cancer. The worst (Grade 3–4) toxicities in 15 patients occurred after the 4th week of radiotherapy. In six of 25 (24%) patients radiation treatments had to be delayed due to toxicities. The median delay of treatment was 10.5 days (range 7–31 days). Of the six patients who had grade 3–4 acute gastrointestinal toxicities, four (66%) had undergone exploratory laparotomy and lymph node sampling prior to start of chemoradiation. We conclude that concomitant EFRT and CDDP appears to be safe with moderate but manageable toxicity. Toxicity is most severe after the 4th week of treatment. Morbidity may be worse in patients with prior laparotomy.